Pengembangan Lembar Kerja Peserta Didik Berbasis Pendekatan Metaphorical Thinking Terhadap Kemampuan Pemecahan Masalah Matematis - Baharudin, Baharudin; Chairuddin, Chairuddin; Tahir, Tahir (JSN : Jurnal Sains Natural, 2024)
This research aims to develop and produce mathematics LKPD (Learner Worksheets) based on the Metaphorical Thinking Approach that meet the criteria of valid, practical and effective in linear program material. This type of research is development research (Research and Development) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The subjects of this research were class XI students at SMA IT Wihdatul Ummah Kolaka, media experts and learning material experts who came from lecturers, mathematics subject teachers. The object of this research is LKPD based on the Metaphorical Thinking approach to linear program material. Data collection instruments include questionnaires and tests. The data obtained was then analyzed using qualitative data analysis techniques and quantitative data analysis techniques. The research results showed that based on the validity test, the LKPD based on the Metaphorical Thinking approach was declared very valid with a percentage level of 89.44%. The results of the small group practicality test using a response questionnaire with a total of 6 students as respondents showed that the LKPD based on the Metaphorical Thinking approach was very practical with a percentage level of 90.42% and the results of the limited group test showed that the LKPD based on the Metaphorical Thinking approach was very practical with a percentage level of 91. 53%. From the calculation results, it appears that 83.33% of students who completed KKM 73 achieved the KKM completion requirements. Based on the overall development process, it can be concluded that the LKPD based on the Metaphorical Thinking approach to linear program material is effective.